An Experience to develop and deliver Clinical Nutrition educational content for medical students - Elham Ehrampoush; Seyed Amin Kouhpayeh; Mojtaba Farjam; Reza Homayounfar; Alireza Ghaemi (Fasa University of Medical Sciences, 2017)
Background & Objective: The duty of physicians in the new world is to promote health, prevent diseases and deliver primary health care. But in accordance with the Edinburgh Declaration, physicians are not trained to deal with these issues. One of the key areas that has an important role in the health of the population, contains the issues related to life style and particularly nutritional issues. Proper nutrition plays a major role in achieving optimal health outcomes and inpatient health care costs will be reduced. This article describes the experience of the implementation and results of the evaluation of providing a course of clinical nutrition for medical students. Material & Methods: This action research study was conducted using census method, in collaboration with 50 students of Fasa University of Medical Sciences in the academic year 96-1395. In this study, clinical nutrition course was presented along with clinical courses for students. The data were gathered through pretest and posttest questionnaire, in each training session, and EDC questionnaire was applied to evaluate students' satisfaction. Descriptive statistics were used to analyze the results of the questionnaires. Results: The comparison of students' score after each training session with pre-test scores, showed a significant increase in students' knowledge of clinical nutrition. Most students' satisfaction was related to the presentation (4.37) and the use of resources (4.32), respectively. Conclusion: The results of this study demonstrated a positive effect of teaching clinical nutrition which can be considered by policymakers to insert this topic in the clinical course for medical students.